Penerapan Media Ular Tangga dalam Meningkatkan Hasil Belajar Siswa Kelas VII di SMP Negeri 2 Tehoru - Fenny Adnina Daulay; Nana Ronawan Rambe (Pencerah, 2023)
This study describes the application of snakes and ladders media in biology subjects with excretion material to improve student learning outcomes. The application of snakes and ladders media aims to increase student motivation and enthusiasm in the teaching and learning process, because it is packaged in learning activities while playing so that it is expected to have a positive impact which can be seen from the increase in student learning outcomes. The study applied classroom action research (CAR) using the Kemmis and M.C. Taggart. The research was conducted at SMP Negeri 2 Tehoru with a population of 30 students in class VII and was carried out in two cycles. Where is the first cycle in the initial test with 13.34% of students who complete with an average value of 45.50. Whereas in the last test of cycle I there was an increase of 76.67% of students who passed with an average score of 67.89 for that reason the research was continued in cycle II and experienced an increase of 90.00% with an average score of 76.33.